Academic dissent in a post COVID-19 world. (November 2021) - Schweinsberg, Stephen; Fennell, David; Hassanli, Najmeh
Abstract: Tourism academia owes its legitimacy to an established process whereby we employ methodologies rigorously to issues within our sphere of interest to apply, test or generate theories. However, what of instances where there are ideological disagreements between scholars, instances where the future of tourism is not set but rather will be framed by scholars on the basis of their own values-based positions? In the present paper an argument is made that scholars should not solely focus on assessing the technical merits of knowledge. Instead we must grapple with what might constitute a 'reasonable dissent' in the context of the "wider habitual in tourism and its scholarship" (Tribe & Liburd, 2017, p. 227). Highlights: A discussion of the interplay of dissenting traditions in society and academic knowledge formation Frameworks for 'reasonable dissent' as evidenced in tourism academia The benefits and challenges in framing 'reasonable' dissents for both the dissenter(s) and the wider tourism academy